Vitamin D3 supplementation and treatment outcomes in patients with depression (D3-vit-dep) - Hansen, Jens Peter (BMC Res Notes, 2019)
OBJECTIVE: To examine whether vitamin D supplementation in patients with depression would result in a reduction in Hamilton D-17 depression score (primary outcome) at 3 and 6 months compared to controls and to explore the correlations between serum vitamin D and symptoms of depression, wellbeing, systolic blood pressure, and waist circumference. In this outpatient multicentre study conducted between 2010 and 2013, patients, 18–65 years old, diagnosed with mild to severe depression were randomly assigned to receive D supplementation 70 micrograms daily or placebo on top of standard treatment. Participants, care givers and those assessing the outcomes were blinded to group assignment. RESULTS: At baseline, 23 patients had a normal 25(OH)D level, 22 had insufficiency (< 25 nmol/L), and 17 had deficiency (25–50 nmol/L). No significant reduction in depression was seen after vitamin D supplementation compared to placebo at Hamilton (18.4–18.0; p = 0.73 at 12 weeks). Vitamin D supplementation did not provide a reduction in symptom score among patients with depression. Trial registration The trial was registered in the National Board of Health (EudraCT: 2011-002585-20) and in ClinicalTrials.Gov (NCT01390662). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-019-4218-z) contains supplementary material, which is available to authorized users.